Education Needs Analysis Through Smart-Phone Applications in Changing Knowledge, Attitude, and Behavior among Patients with Diabetes Mellitus - Mahendro Prasetyo Kusumo; Najib Budhi Wardoyo (Universitas Aisyah Pringsewu, 2023)
Introduction: Diabetes Mellitus is one of the non-communicable diseases which is currently increasing in number. DM is a precursor of other diseases such as hypertension, heart disease, and stroke. Uncontrolled DM causes comprehensive complications. Increased knowledge, attitudes, and correct actions from patients and families are needed to prevent disease complications. Objective: This study aims to analyze the educational needs through information technology-based applications in DM patients in changing knowledge, attitudes, and behavior. Methods: This study uses a quantitative method with a cross-sectional design. The study population was all DM patients at Aisyiyah Kudus Hospital in October 2022 with a total of 106 patients. Samples were taken by a simple random sampling of 84 respondents who met the inclusion criteria. Univariate analysis was used to determine the level of knowledge, attitudes, and behavior. Bivariate analysis was used to compare DM patients' education level, knowledge, attitudes, and behavior. Results: The result showed no significant difference between knowledge, attitude, and behavior (p-value=0.322) based on education level. The result of this research is expected to provide health education through the E-MMCD application for diabetes mellitus patients to increase their knowledge, attitude, and behavior. Health education is also needed to prevent the disease from getting worse. Abstrak: Pendahuluan: Diabetes Mellitus (DM) merupakan salah satu penyakit tidak menular (PTM) yang saat ini jumlahnya semakin meningkat. DM merupakan prekursor penyakit lain seperti Hipertensi, penyakit jantung, dan stroke. DM yang tidak terkontrol menyebabkan komplikasi yang bersifat menyeluruh. Peningkatan pengetahuan, sikap, dan tindakan yang benar dari pasien dan keluarga sangat diperlukan untuk mencegah terjadinya komplikasi penyakit. Tujuan: Penelitian ini bertujuan untuk menganalisis kebutuhan edukasi melalui aplikasi berbasis teknologi informasi (E-MMCD/Electronic Muhammadiyah Monitoring Chronic Disease) pada pasien DM dalam mengubah pengetahuan, sikap, dan perilaku. Metode: Penelitian ini menggunakan metode kuantitatif dengan desain cross sectional. Populasi penelitian adalah seluruh pasien DM di RS Aisyiyah Kudus bulan Oktober 2022 dengan jumlah 106 pasien. Sampel diambil dengan cara acak sederhana dan sampel sebanyak 84 responden memenuhi kriteria inklusi. Untuk mengetahui tingkat pengetahuan, sikap, dan perilaku digunakan analisis univariat dan bivariat untuk melihat perbedaan tingkat pendidikan dengan pengetahuan, sikap, dan perilaku penderita DM. Hasil: Hasil uji statistik Kruskal Wallis menunjukkan tidak ada perbedaan yang signifikan antara pengetahuan (p-value = 0,194), sikap (p-value 1,091), dan perilaku (p-value = 0,322) berdasarkan tingkat pendidikan. Penelitian ini berharap pemberian edukasi kesehatan melalui aplikasi E-MMCD dapat meningkatkan pengetahuan, sikap, dan perilaku penderita DM. Pendidikan kesehatan juga diperlukan untuk mencegah memburuknya kondisi penyakit DM.